How autonomous actions influence the strategy formulation process in the management of public administration distance learning course at Universidade Federal de Santa Catarina, Brazil (Gestão & Regionalidade, 2017)
This study aimed to analyze how the autonomous actions influence the strategy formation process in the management of Public Administration Distance Learning Course at Universidade Federal de Santa Catarina. A qualitative methodology was adopted by means of a case study. The selection of the case was carried out intentionally and for convenience. The data collection techniques used were document research and semi-structured script interviews with a representative from each hierarchical level. Data analysis was performed through narrative analysis and pattern-matching technique. The autonomous actions allow modifying the strategy of the organization and making it more flexible because it presents information and events of the daily routine which often run away from what was planned. The results showed the proposition established that the autonomous actions influence and change the strategy formation process, contributing positively to the course's management and processes.